1999
DOI: 10.1152/jappl.1999.86.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial fluid clearance persists in the presence of moderate left atrial hypertension in sheep

Abstract: The effect of moderate left atrial (LA) hypertension on alveolar liquid clearance (ALC) was investigated in anesthetized, ventilated sheep, surgically prepared to measure lung lymph flow as well as hemodynamics. To simulate alveolar edema, 3-4 ml/kg of isosmolar 5% albumin in Ringer lactate were instilled into each lower lobe, and ALC was measured. After 4 h of LA hypertension (24 cmH2O), ALC was similar to that in control sheep (31 +/- 3% with LA hypertension vs. 34 +/- 10% with normal LA pressure). Because p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 38 publications
7
58
1
Order By: Relevance
“…In the lung recipient, pulmonary edema due to reperfusion lung injury occurs in 15-35% of recipients and is a major cause of primary graft failure, morbidity, and mortality in the lung transplant population (39). ␤-Adrenergic agonists have been shown to enhance the resolution of pulmonary edema experimentally (6,8,33) and have a good safety profile in critically ill patients (10,19). Furthermore, the clinical utility of ␤-adrenergic agonists for one type of pulmonary edema has now been demonstrated: inhalation of the ␤-agonist salmeterol was recently shown to reduce the incidence of high-altitude pulmonary edema in those at risk (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the lung recipient, pulmonary edema due to reperfusion lung injury occurs in 15-35% of recipients and is a major cause of primary graft failure, morbidity, and mortality in the lung transplant population (39). ␤-Adrenergic agonists have been shown to enhance the resolution of pulmonary edema experimentally (6,8,33) and have a good safety profile in critically ill patients (10,19). Furthermore, the clinical utility of ␤-adrenergic agonists for one type of pulmonary edema has now been demonstrated: inhalation of the ␤-agonist salmeterol was recently shown to reduce the incidence of high-altitude pulmonary edema in those at risk (35).…”
Section: Discussionmentioning
confidence: 99%
“…These include acute elevation of left atrial pressure (8,41), the creation of systemic left-to-right shunts (3), rapid electrical pacing of the heart (43-45), supracoronary aortic banding (24), as well as the coronary ligation technique used in this study. With respect to the lung's ability to clear alveolar fluid, acute increases in left atrial pressure have been shown to either depress baseline alveolar fluid clearance or inhibit the ability of ␤-adrenergic agonists to increase alveolar fluid clearance, whereas longer-term studies have shown either maintenance of or increased alveolar fluid clearance.…”
Section: L490mentioning
confidence: 99%
“…4 Betaadrenergic agonists increase vectorial sodium transport in vitro, 5 enhance the clearance of alveolar fluid in the resected human lung 6 and in several species of animals, [7][8][9][10] and accelerate the resolution of pulmonary edema in animal models of lung injury. [11][12][13][14][15] However, the effects of beta-adrenergic agonists in the treatment of pulmonary edema in humans have not been assessed, and information demonstrating the importance of this vectorial sodium transport in the development of and recovery from pulmonary edema in humans is sparse and indirect. 16,17 In a double-blind, placebo-controlled study, we tested whether the prophylactic inhalation of the betaadrenergic agonist salmeterol at a dose shown to stimulate the clearance of alveolar fluid 18 decreases the incidence of pulmonary edema during exposure to high altitudes in subjects who are prone to high-altitude pulmonary edema.…”
Section: Resultsmentioning
confidence: 99%
“…2). [11][12][13][14][15] It is also possible that salmeterol, by improving alveolar ventilation and reducing alveolar hypoxia at high altitude, attenuates the hypoxiainduced impairment of alveolar absorption of sodium and fluid 27 in these subjects. Alternatively, salmeterol *Plus-minus values are means ±SD.…”
Section: Discussionmentioning
confidence: 99%